2021
DOI: 10.1038/s41598-021-82481-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidised self-lipids and alveolar macrophage CD1b expression in COPD

Abstract: In chronic obstructive pulmonary disease (COPD) apoptotic bronchial epithelial cells are increased, and their phagocytosis by alveolar macrophages (AM) is decreased alongside bacterial phagocytosis. Epithelial cellular lipids, including those exposed on uncleared apoptotic bodies, can become oxidized, and may be recognized and presented as non-self by antigen presenting cells. CD1b is a lipid-presenting protein, previously only described in dendritic cells. We investigated whether CD1b is upregulated in COPD A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…These oxidation-specific components are recognized as endogenous DAMPs by PRR in phagocytic cells acting as antigen-presenting cells (APCs) to over-stimulate the innate immune cells (26). Recent evidence reported that CD1b in dendritic cells play a role in oxidizing lipids that stimulate NKT cells (27). Leiw et al reported that selfantigenic lipids are associated with CD1d that promotes NKT cell participation in restoring tissue homeostasis after a sterile injury (28).…”
Section: Acute Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…These oxidation-specific components are recognized as endogenous DAMPs by PRR in phagocytic cells acting as antigen-presenting cells (APCs) to over-stimulate the innate immune cells (26). Recent evidence reported that CD1b in dendritic cells play a role in oxidizing lipids that stimulate NKT cells (27). Leiw et al reported that selfantigenic lipids are associated with CD1d that promotes NKT cell participation in restoring tissue homeostasis after a sterile injury (28).…”
Section: Acute Inflammationmentioning
confidence: 99%
“…These oxidation-specific components are recognized as endogenous DAMPs by PRR in phagocytic cells acting as antigen-presenting cells (APCs) to over-stimulate the innate immune cells ( 26 ). Recent evidence reported that CD1b in dendritic cells play a role in oxidizing lipids that stimulate NKT cells ( 27 ). Leiw et al.…”
Section: Acute Inflammationmentioning
confidence: 99%
“…It was proposed that cigarette smoke exposure increases phospholipid oxidation, which hinders its surface tension-lowering ability [138]. Indeed, BALF isolated from mice exposed to cigarette smoke for 2 weeks was found to contain high levels of oxidised PC and in vitro treatment of alveolar macrophages with oxidised lipids and phospholipids led to reduced cell viability, decreased respiratory burst upon LPS stimulation and impaired bacterial killing [94,139]. Similarly, several studies have observed that direct in vitro treatment of surfactant with cigarette smoke led to dose-dependent alterations in surfactant interfacial properties and microstructure leading to reduced surface activity [140][141][142][143].…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Tobacco smoke is a complex, not fully studied mixture of several thousand different chemicals, including many free radicals, which can have a significant effect on the lipids of the lungs [ 35 ]. Exposure to cigarette smoke causes lipid peroxidation in the bronchial epithelium and also leads to the redistribution of various lipid fractions [ 36 ].…”
Section: Lipid Metabolism and Its Disorders In Copdmentioning
confidence: 99%
“…It has been shown that exposure to cigarette smoke causes the production of antibodies against oxidized lipids in the lungs of mice, which may contribute to limiting the response to damaged lipids [ 230 ]. Interestingly, the phagocytic function of macrophages was dose-dependent suppressed by the presence of oxidized epithelial lipids [ 36 ].…”
Section: Participation Of Lipids In Phagocytosis Disorders In Copdmentioning
confidence: 99%